Analisis Kesalahan Istilah Penelitian Dalam Skripsi Mahasiswa Pendidikan Bahasa Arab UIN Raden Intan Lampung Angkatan 2018 - Najah, Zughrofiyatun; Aditya, Viqri; Basyar, Syarifudin (STAI Tebing Tinggi Deli, 2024)
This study is the result of research that describes what are the errors in the use of research terms in the theses of Arabic language education students at UIN Raden Intan Lampung. Language error analysis is the process of identifying, analyzing, and understanding errors that occur in language use, both in writing and conversation. The understanding of grammatical errors, vocabulary, spelling, syntax, and improper use of idioms. Where these language errors are often seen in the writing of scientific papers or theses. The background of the author to make this thesis is based on observations and readings made by the author on errors or inaccuracies in the use of research terms in the theses of Arabic language education students in the central library of UIN Raden Intan Lampung. Where the use of Arabic research terms is not maximized so that repeated errors occur in the thesis or scientific work. This research uses descriptive qualitative methods with data collection methods, namely reading and writing, and documentation. The population in this study is the thesis of Arabic Language Education students class of 2018 and the sample in this study is as many as 15 theses class of 2018 and additional data 10 theses class of 2023, using data collection techniques, data grouping, and drawing conclusions. The results of this study show that the use of the term thesis in writing the thesis of Arabic Language Education students still has many repeated mistakes. Of the 25 theses of Arabic language education students in 2018 and 2023, researchers found 24 errors, 6 errors in vocabulary selection and 18 errors in grammar (ibaroh). With this research, it can be a positive impact for students in the use of thesis research terms and can also be a source of easy improvement recommendations where repeated errors are expected to be minimized again and are expected to be eliminated. Hopefully, the interest and enthusiasm of researchers can make students' scientific work more qualified so that readers can more easily understand the contents of the theses that have been made.